Enhancing Vocabulary Mastery in Elementary Students through Liveworksheets - Aditya, Restu Wahyu Tresna (English Education Department STKIP Agama Hindu Singaraja, 2025)
This study examines the effect of implementing Liveworksheets on the English vocabulary mastery of fourth-grade students at SD Negeri 1 Astina. Utilizing a quasi-experimental design with a post-test-only control group, the research involved a sample of 54 students, evenly distributed into an experimental group and a control group, each comprising 27 participants. Data were collected through a vocabulary post-test, and the results were analyzed using inferential statistical methods via IBM SPSS Statistics 26. The findings reveal that the experimental group achieved a significantly higher mean post-test score (M = 87.03) compared to the control group (M = 71.66). The independent samples t-test indicated a statistically significant difference between the groups (p = 0.000). Additionally, the effect size computed using Cohen’s d (1.926) reflects a large impact of the intervention. These results suggest that Liveworksheets, as an interactive digital learning tool, substantially enhances students’ mastery of English vocabulary. In conclusion, the implementation of Liveworksheets proves to be an effective pedagogical strategy to improve vocabulary acquisition among elementary students. The significant improvement observed in the experimental group underscores the potential of interactive digital tools to foster more engaging and effective learning environments. Educators are encouraged to integrate such technology-based interventions to augment traditional teaching methods and optimize student outcomes in language learning.